Torilin Inhibits Inflammation by Limiting TAK1-Mediated MAP Kinase and NF-κB Activation - Mehari Endale; Tae-Hwan Kim; Yi-Seong Kwak; Na-Mi Kim; Seung-Hyung Kim; Jae Youl Cho; Bong-Sik Yun; Man-Hee Rhee (Mediators of Inflammation)
Torilin, a sesquiterpene isolated from the fruits of Torilis japonica, has shown antimicrobial, anticancer, and anti-inflammatory properties. However, data on the mechanism of torilin action against inflammation is limited. This study aimed at determining the anti-inflammatory property of torilin in LPS-induced inflammation using in vitro model of inflammation. We examined torilin’s effect on expression levels of inflammatory mediators and cytokines in LPS-stimulated RAW 264.7 macrophages. The involvement of NF-kB and AP-1, MAP kinases, and adaptor proteins were assessed. Torilin strongly inhibited LPS-induced NO release, iNOS, PGE2, COX-2, NF-α, IL-1β, IL-6, and GM-CSF gene and protein expressions. In addition, MAPKs were also suppressed by torilin pretreatment. Involvement of ERK1/2, P38MAPK, and JNK1/2 was further confirmed by PD98059, SB203580, and SP600125 mediated suppression of iNOS and COX-2 proteins. Furthermore, torilin attenuated NF-kB and AP-1 translocation, DNA binding, and reporter gene transcription. Interestingly, torilin inhibited TAK1 kinase activation with the subsequent suppression of MAPK-mediated JNK, p38, ERK1/2, and AP-1 (ATF-2 and c-jun) activation and IKK-mediated I-κBα degradation, p65/p50 activation, and translocation. Together, the results revealed the suppression of NF-κB and AP-1 regulated inflammatory mediator and cytokine expressions, suggesting the test compound’s potential as a candidate anti-inflammatory agent.